Ущерб, причиненный войной, и политика реституций и репараций Югославии [War Damage and the Policy of Restitution and Reparations in Yugoslavia] - Živković, Nikolaj (Studia Historiae Oeconomicae, 1979)
This article analyzes the damage suffered by Yugoslavia as a result of World War II, as well as the post-war policies of restitution and reparations. The author examines both the material and human losses inflicted by Nazi occupation and evaluates the effectiveness of international mechanisms used to seek compensation. The aim of the study is to provide a comprehensive assessment of the scale of destruction and losses, and to analyze the legal and political instruments through which Yugoslavia attempted to recover damages. The research is based on archival documents, international treaties, materials from the 1945 Paris Conference, and inter-Allied agreements. The article outlines the forms of occupational exploitation — including mass extermination of civilians, deportations, forced labor, and the destruction of infrastructure and cultural assets. It presents concrete data on human losses (more than 1.7 million dead) and economic damages. Yugoslavia suffered one of the highest levels of material loss among the Allied nations — over 9 billion, placing it second only to France. The analysis shows that despite Yugoslavia’s participation in international conferences and the existence of legal grounds for claims, the country did not receive adequate compensation. The reparations mechanisms proved limited and primarily served the interests of the major powers. The author concludes that the just restoration of violated rights was only partially realized.